Business Resilience amid Global Crises: Between Adaptation, Innovation, and Legal Certainty - Ony Thoyib Hadi Wijaya; Kirana Salsabilla Citra Wijaya; Lely Maharani (MUARA EKONOMI : Jurnal Ilmiah Ilmu Ekonomi, Manajemen & Bisnis, 2026)
Global economic crises, geopolitical tensions, and fluctuations in international markets have generated significant uncertainty for the business sector. Many business actors have experienced decline and even bankruptcy; however, certain sectors have demonstrated remarkable resilience and sustained growth. This article aims to examine business resilience amid global crises through an interdisciplinary approach that integrates economic theory, organizational adaptation, and business law. Drawing on the grand theory of economic utilitarianism, this study argues that business sectors providing essential goods and services play a substantial role in social welfare and therefore tend to be more resilient during periods of crisis. Furthermore, through the middle-range theories of organizational adaptation and contingency, this article highlights flexibility, innovation, and the ability to respond to environmental changes as key determinants of business survival. From a legal perspective, compliance with business law, including consumer protection, electronic transactions, and regulatory certainty, should not be viewed as an obstacle, but rather as a stabilizing instrument that fosters public trust and institutional legitimacy. Employing a normative-juridical method and qualitative analysis based on secondary data, this article concludes that businesses capable of integrating adaptation, innovation, legal compliance, and social responsibility are more likely to achieve long-term sustainability, even in times of global crisis